(untitled) (Experimental biology, 2022)
In Kazakhstan, the production of organic melon products is at the beginning of development. The most open and regulated elements of biological melon cultivation in the production environment include the use of organic fertilizers and biological products instead of chemical ones. The data received in the process of scientific research showed that the use of organic and biological fertilizers helped to raise fresh plants and process acceleration of fruit ripening by an average of 3-5 days. The productivity of melon grew to 37.32% with biologized fertilizer systems. So, the quality of melon fruits has increased for the non-fertilized control. Рroviding the low cost and high payback of organic fertilizers, the positive influence on the productivity and ecological purity of the cultivated products, we can do a conclusion about the potential transition of the melon industry of the country from traditional ways of cultivation to alternative ones.